Acute Compartment Syndrome: An Expert Survey of Orthopaedic Trauma Association Members. Issue 5 (May 2018) - Collinge, Cory A.; Attum, Basem; Lebus, George F.; Tornetta, Paul; Obremskey, William; Ahn, Jaimo; Mirick, Gudrun; Schmidt, Andrew; Spitler, Clay; Coles, Chad; Krause, Peter
Abstract : Objectives: The goal of this study was to describe current opinions of orthopaedic trauma experts regarding acute compartment syndrome (ACS). Design: Web-based survey. Participants: Active Orthopaedic Trauma Association (OTA) members. Methods: A 25-item web-based questionnaire was advertised to active members of the OTA. Using a cross-sectional survey study design, we evaluated the perceived importance of ACS, as well as preferences in diagnosis and treatment. Results: One hundred thirty-nine of 596 active OTA members (23%) completed the survey. ACS was believed to be clinically important and with severe sequelae, if missed. Responses indicated that diagnosis should be based on physical examination in an awake patient, and that intracompartmental pressure testing was valuable in the obtunded or unconscious patient. The diagnosis of ACS with monitoring should be made using the difference between diastolic blood pressure and intracompartmental pressure (ΔP) of ⩽30 mm Hg. Once ACS is diagnosed, respondents indicated that fasciotomies should be performed as quickly as is reasonable (within 2 hours). The consensus for wound management was closure or skin grafting within 1–5 days later, and skin grafting was universally recommended if closure was delayed to >7 days. Conclusions: ACS is a challenging problem with poor outcomes if missed or inadequately treated. OTA members demonstrated agreement to many diagnostic and treatment choices for ACS. Level of Evidence: Therapeutic Level V. See Instructions for Authors for a complete description of the levels of evidence.